2017
DOI: 10.1597/16-115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Renal and Cervical Vertebral Anomalies in Patients with Isolated Microtia and/or Aural Atresia

Abstract: The data suggest that there is no increased prevalence of structural renal or cervical vertebral anomalies in patients with isolated microtia and/or aural atresia. Therefore, these patients do not require routine screening renal ultrasound or cervical spine X-rays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…These anomalies resolved over the course of subsequent follow-up, and the authors concluded that renal ultrasound may not be necessary in patients with isolated microtia. 10 Similarly, a more recent study revealed that 7% of patients with isolated microtia had renal abnormalities. 11 Our results show a higher incidence of these findings, albeit with a limited sample size.…”
Section: Discussionmentioning
confidence: 96%
“…These anomalies resolved over the course of subsequent follow-up, and the authors concluded that renal ultrasound may not be necessary in patients with isolated microtia. 10 Similarly, a more recent study revealed that 7% of patients with isolated microtia had renal abnormalities. 11 Our results show a higher incidence of these findings, albeit with a limited sample size.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that clinicians should perform renal ultrasound in patients with syndromic and nonsyndromic microtia, as 16%–29% of such patients have kidney abnormalities (Koening et al, 2018; Wang et al, 2001). At least one research group found that spinal X‐ray was not justified due to the lack of associated vertebral abnormalities in their study population (Zim et al, 2017). However, another group recommended that complete spinal X‐ray and a renal ultrasound should be performed when craniofacial microsomia is detected, because vertebral (47%) and genitourinary (29%) abnormalities were clearly noted in such cases (Cohen et al, 2017) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested clinical approaches for patients with microtia and/or craniofacial microsomia (Cohen et al, 2017; Heike et al, 2013; Koening et al, 2018; Wang et al, 2001; Zim et al, 2017). However, we currently lack any consensus on which imaging studies (orthopantomography, full spine X‐ray, renal ultrasound) should be performed in patients with microtia/OAVS and their parents or other relatives as part of a comprehensive clinical approach to rule out variable expressivity and adequately classify “sporadic” versus “familial” patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most common syndromes associated with microtia are Townes-Brock syndrome, Goldenhar syndrome (oculoauriculovertebral spectrum), Treacher Collins and branchio-oto-renal syndrome [6,22,23].…”
Section: J Clinical Otorhinolaryngologymentioning
confidence: 99%